Some Applications of a new class of Univalent Functions Defined by Subordination Property (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we introduce and study some applications of a new class of univalent functions defined by subordination property. Coefficient inequality, convex linear combinations, growth and distortion inequalities, radii of starlikeness, convexity and close-to- convexity and Hadamard product (or convolution) are given.